Positive Schizotypy Increases the Acceptance of Unpresented Materials in False Memory Tasks in Non-clinical Individuals - Rodríguez-Ferreiro, Javier; Aguilera, Mari; Davies, Robert (Frontiers in Psychology, 2020)
Enhanced spreading of semantic activation has been hypothesized to underlie some of the most significant symptoms of schizotypal personality, like thought disorder, odd speech, delusion, or magical thinking. We applied the Deese/Roediger-McDermott false memory task to the study of semantic activation in a group of 123 non-clinical individuals varying in the three dimensions of schizotypal personality: positive, negative and disorganized schizotypy. In the study phase, we presented them with lists composed of words semantically associated to unpresented critical words. Then, they responded to a recognition questionnaire including previously presented words and critical unpresented lures, as well as weakly related and unrelated unpresented lures. Participants rated their confidence in recognizing each word. They also filled in a standardized schizotypal personality questionnaire. Confirming the false memory effect, recognition ratings provided in response to critical words were higher than those produced for both weakly related and unrelated items. Crucially, scores in the positive dimension increased recognition percentages and confidence ratings for weakly related and unrelated lures. This study indicates that high levels of positive schizotypy might influence the tendency to accept false memories of unrelated unpresented material.